2012
DOI: 10.1111/j.1740-8261.2011.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Metallic Artifact of Commonly Encountered Surgical Implants and Foreign Material

Abstract: Magnetic resonance imaging (MRI) artifacts secondary to metallic implants and foreign bodies are well described. Herein, we provide quantitative data from veterinary implants including total hip arthroplasty implants, cranial cruciate repair implants, surgical screws, a skin staple, ligation clips, an identification microchip, ameroid constrictor, and potential foreign bodies including air gun and BB projectiles and a sewing needle. The objects were scanned in a gelatin phantom with plastic grid using standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
0
14
0
4
Order By: Relevance
“…There are several disadvantages and limitations of the T2* sequence: it has an inherently low signal‐to‐noise ratio, which likely accounts for the inability to discern some of the parenchymal lesions seen on T2 and FLAIR in this study; any para‐ or ferromagnetic material or air‐brain interfaces near the field of view will result in marked susceptibility artifact, which can impair interpretation or even render the sequence nondiagnostic, as occurred in one of the cases in this study , . In addition, the susceptibility artifact can “bloom,” making the size or internal characteristics of a lesion difficult to determine, and it is often not possible to accurately age a hemorrhagic lesion based on T2*‐weighted images since there can be overlap among the appearances of different stages of hemorrhage on T2* .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are several disadvantages and limitations of the T2* sequence: it has an inherently low signal‐to‐noise ratio, which likely accounts for the inability to discern some of the parenchymal lesions seen on T2 and FLAIR in this study; any para‐ or ferromagnetic material or air‐brain interfaces near the field of view will result in marked susceptibility artifact, which can impair interpretation or even render the sequence nondiagnostic, as occurred in one of the cases in this study , . In addition, the susceptibility artifact can “bloom,” making the size or internal characteristics of a lesion difficult to determine, and it is often not possible to accurately age a hemorrhagic lesion based on T2*‐weighted images since there can be overlap among the appearances of different stages of hemorrhage on T2* .…”
Section: Discussionmentioning
confidence: 94%
“…There are several disadvantages and limitations of the T2 * sequence: it has an inherently low signal-to-noise ratio, which likely accounts for the inability to discern some of the parenchymal lesions seen on T2 and FLAIR in this study; any para-or ferromagnetic material or air-brain interfaces near the field of view will result in marked susceptibility artifact, which can impair interpretation or even render the sequence nondiagnostic, as occurred in one of the cases in this study. 23,24,[65][66][67] In addition, the susceptibility artifact can "bloom," making the size or internal characteristics of a lesion difficult to determine, and it is often not possible to accurately age a hemorrhagic lesion based on T2 * -weighted images since there can be overlap among the appearances of different stages of hemorrhage on T2 * . 23,68 An additional problem encountered with the T2 * -weighted gradient recalled echo sequence was misinterpretation of normal structures as pseudolesions, leading to the conclusion that subtle parenchymal changes not associated with susceptibility artifact on T2 * -weighted images should be interpreted with caution and should always be compared to sequences with better soft tissue contrast and signal-tonoise ratio.…”
Section: Discussionmentioning
confidence: 99%
“…For example, metallic structures may result in artifacts such as geometrical distortion, central areas of signal loss, and peripheral linear hyperintensities due to differences in magnetic susceptibility between normal tissue and implant. [12][13][14] Tantalum cages are known to produce drastically less distortion of MR images than stainless steel or titanium implants because they have lower magnetic susceptibility. Although previous authors have suggested that this artifact is negligible, our experience has been different, particularly at the surgical level (Fig.…”
mentioning
confidence: 99%
“…Einfluss der Phasen-/Frequenzkodierung: Wird die Phasenkodierung in y-Richtung (Frequenzkodierung in z-Richtung) und vertikal zur Längsachse des metallischen Objekts gewählt, können größere Suszeptibilitätsartefakte verursacht werden (2,31,32). Mit der dreidimensionalen Messmethode ließ sich dies bei SE-Sequenzen nachvollziehen.…”
Section: Diskussionunclassified